Investigation of strain gauge measurement on paper-based sensor with various thickness of carbon based conductive paint - Jamaluddin, Muhammad Nazrul Hisyam; Mohd Salleh, Mohd Hazimin; Mohamad, Samsun Baharin (Malaysian Society for Sensor Technology Development (SENSOR), 2023)
Strain sensor has been utilized in various applications, such as in healthcare monitoring, materials science experiment and environmental detection due to their durability, flexibility and affordable cost to consumers. Researchers have investigated that electrical conductive paints could alter the constantan alloy electrical resistance when subjected to mechanical strain. The conductive particles in the mixtures create the conductivity charateristic in its networks. When mechanical deformation occurs, it will change the material’s electrical properties. In this research, we aim to study the effect of the carbon conductive paint paper-based strain sensor as a sensor coil in the fabricated device. Investigation of electrical resistance R as the length of the sensor altered and strain at specific angle was conducted. The specific conductive paint was painted on top of A4 printing paper, 80gsm. There were three sensor designs and two paint thicknesses which were 1 layer and 5 layers that have been premeditated. In the first experiment, the gauge factor design one was 0.67, followed by 0.33 and 0.50. All sensors were painted with 1 layer of conductive paint. For the 5 layers of the painted sensor, the gauge factor started with 0.47, then 0.16, and followed by 1.5. In conclusion, the suitable sensor design and thickness is the third design with 5 layers of painted conductive paint showed the highest sensitivity among the others.